2021
DOI: 10.1038/s41531-020-00152-9
|View full text |Cite
|
Sign up to set email alerts
|

Stress and mindfulness in Parkinson’s disease – a survey in 5000 patients

Abstract: Many Parkinson’s disease (PD) patients notice that motor symptoms worsen during stress, and experience stress-related neuropsychiatric symptoms such as anxiety and depression. Here we investigated which personal and disease characteristics are associated with perceived stress in PD, which PD symptoms are sensitive to stress, and we assessed self-reported benefits of stress-reducing strategies such as mindfulness. We sent an online survey to the Fox Insight cohort (n = 28,385 PD patients, n = 11,413 healthy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 60 publications
(28 reference statements)
2
18
0
Order By: Relevance
“…The response rate of 5.7% of this study was within the range of previous, comparable questionnaire studies of PD clientele [ 45 , 46 , 47 ]. Interestingly, the response rate resembled that of a recent questionnaire-based study (4.7%) using the same distribution method via the members’ journal of the German Parkinson Association but addressing a completely different topic [ 48 ].…”
Section: Discussionsupporting
confidence: 84%
“…The response rate of 5.7% of this study was within the range of previous, comparable questionnaire studies of PD clientele [ 45 , 46 , 47 ]. Interestingly, the response rate resembled that of a recent questionnaire-based study (4.7%) using the same distribution method via the members’ journal of the German Parkinson Association but addressing a completely different topic [ 48 ].…”
Section: Discussionsupporting
confidence: 84%
“…A high beta band oscillation strength in the STN of patients with PD is correlated with the severity of motor symptoms, especially rigidity and bradykinesia (Kuhn et al, 2006). The strength of the beta band oscillation is influenced not only by movement (Feingold et al, 2015) or dopaminergic drugs (Weinberger et al, 2006), but also by several other factors (Urrestarazu et al, 2009;Duprez et al, 2019;Benis et al, 2020). A previous study has suggested that PD motor symptoms worsened when patients were subjected to stress (van der Heide et al, 2021), while training and relaxation programs mitigated motor symptoms of PD (Reuter et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…PD rest tremor typically increases during cognitive tasks or motor coactivation, e.g., counting or tapping with the contralateral hand, and this can be used by clinicians to bring out the tremor in the clinic ( Dirkx et al, 2020 ). PD tremor is very sensitive to stress, and it can be reduced with stress-reducing interventions such as mindfulness ( van der Heide et al, 2021 ) and relaxation exercises ( Blakemore et al, 2019 ). Patients with PD may also manifest tremor in the cranio-cervical area, including chin, tongue, and voice tremor.…”
Section: Tremor In Parkinson’s Disease and Parkinsonismmentioning
confidence: 99%